2013
DOI: 10.1021/es400120m
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Photodegradable and Biodegradable Organic Nitrogen in Wastewater Effluents

Abstract: Photochemical degradation of dissolved organic nitrogen (DON) in final effluent of trickling filter and activated sludge wastewater treatment plants (WWTPs) was studied. Inorganic N, mostly nitrite, was produced from the photodegradation of DON for samples from both WWTPs. Photodegradable DON (PDON), biodegradable DON (BDON), and overlapping photodegradable-biodegradable DON (OPBDON) were determined. BDON was associated with PDON as well as non-PDON. BDON and PDON concentrations in the final effluent samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
(99 reference statements)
1
9
1
Order By: Relevance
“…Calculations show that both disinfection methods can significantly (p , 0.05) increase concentrations of LMW-N and decrease concentrations of DON (Table 2). It is likely that UV disinfection results in the breakdown of DON in a similar fashion to the breakdown that occurs during natural UV exposure (Simsek et al, 2013). This study's results differ from that of Sattayatewa et al (2010), which showed no changes in DON concentration after UV disinfection, which could be attributed to low UV dosage and contact time (Simsek et al, 2013).…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…Calculations show that both disinfection methods can significantly (p , 0.05) increase concentrations of LMW-N and decrease concentrations of DON (Table 2). It is likely that UV disinfection results in the breakdown of DON in a similar fashion to the breakdown that occurs during natural UV exposure (Simsek et al, 2013). This study's results differ from that of Sattayatewa et al (2010), which showed no changes in DON concentration after UV disinfection, which could be attributed to low UV dosage and contact time (Simsek et al, 2013).…”
Section: Resultscontrasting
confidence: 67%
“…It is likely that UV disinfection results in the breakdown of DON in a similar fashion to the breakdown that occurs during natural UV exposure (Simsek et al, 2013). This study's results differ from that of Sattayatewa et al (2010), which showed no changes in DON concentration after UV disinfection, which could be attributed to low UV dosage and contact time (Simsek et al, 2013). If a fraction of DON is converted to inorganic LMW-N as a result of UV disinfection, there will be less DON released into the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Photodegradation of the DOM of diverse terrigenous sources has been demonstrated to affect the growth and metabolism of bacteria in aquatic ecosystems (Lindell et al, 1995 ; Scully et al, 2003 ; Anesio et al, 2005 ; Lønborg et al, 2013 , 2016 ; Simsek et al, 2013 ). However, no study to date has provided bacterial transcriptomic or mutational changes occurring after exposure to sunlight irradiated DOM.…”
Section: Discussionmentioning
confidence: 99%
“…rDON has emerged as a topic of interest for facilities that are required to meet strict effluent TN limits (<3 mg/L), since rDON can represent between 0.5 and 1 mg N/L of the effluent N (Sattayatewa et al, 2010). A fraction of the rDON (up to 10%) can also be converted by advanced oxidation processes such as ozonation or H 2 O 2 -UV treatment to a form that is susceptible to further biological transformation (Simsek et al, 2013). Removal of rDON from AS plant effluent can be achieved using enhanced coagulation and flocculation and activated carbon treatment .…”
Section: Refractory Dissolved Organic Nmentioning
confidence: 99%